Liquid biopsy of peripheral blood using mass spectrometry detects primary extramedullary disease in multiple myeloma patients - Vlachová, Monika; Pečinka, Lukáš; Gregorová, Jana; Moráň, Lukáš; Růžičková, Tereza; Kovačovicová, Petra; Almáši, Martina; Pour, Luděk; Štork, Martin; Hájek, Roman; Jelínek, Tomáš; Popková, Tereza; et al. (Scientific reports, 2024)
Multiple myeloma (MM) is the second most prevalent hematological malignancy, characterized by infiltration of the bone marrow by malignant plasma cells. Extramedullary disease (EMD) represents a more aggressive condition involving the migration of a subclone of plasma cells to paraskeletal or extraskeletal sites. Liquid biopsies could improve and speed diagnosis, as they can better capture the disease heterogeneity while lowering patients' discomfort due to minimal invasiveness. Recent studies have confirmed alterations in the proteome across various malignancies, suggesting specific changes in protein classes. In this study, we show that MALDI-TOF mass spectrometry fingerprinting of peripheral blood can differentiate between MM and primary EMD patients. We constructed a predictive model using a supervised learning method, partial least squares-discriminant analysis (PLS-DA) and evaluated its generalization performance on a test dataset. The outcome of this analysis is a method that predicts specifically primary EMD with high sensitivity (86.4%), accuracy (78.4%), and specificity (72.4%). Given the simplicity of this approach and its minimally invasive character, this method provides rapid identification of primary EMD and could prove helpful in clinical practice.
Keywords: Biomarkers, Tumor; lidé středního věku; lidé; spektrometrie hmotnostní - ionizace laserem za účasti matrice; senioři; mužské pohlaví; Multiple Myeloma; Liquid Biopsy; Male; mnohočetný myelom; nádorové biomarkery; Female; tekutá biopsie; Aged; Middle Aged; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; ženské pohlaví; Humans